Cartilage-specific deletion of ephrin-B2 in mice results in early developmental defects and an osteoarthritis-like phenotype during aging in vivo. Issue 1 (December 2016) - Valverde-Franco, Gladys; Lussier, Bertrand; Hum, David; Wu, Jiangping; Hamadjida, Adjia; Dancause, Numa; Fahmi, Hassan; Kapoor, Mohit; Pelletier, Jean-Pierre; Martel-Pelletier, Johanne
Abstract Background Ephrins and their related receptors have been implicated in some developmental events. We have demonstrated that ephrin-B2 (EFNB2) could play a role in knee joint pathology associated with osteoarthritis (OA). Here, we delineate the in vivo role of EFNB2 in musculoskeletal growth, development, and in OA using a cartilage-specific EFNB2 knockout (EFNB2Col2 KO) mouse model. Methods EFNB2Col2 KO was generated with Col2a1-Cre transgenic mice. The skeletal development was evaluated using macroscopy, immunohistochemistry, histomorphometry, radiology, densitometry, and micro-computed tomography. Analyses were performed at P0 (birth) and on postnatal days P15, P21, and on 8-week- and 1-year-old mice. Results EFNB2Col2 KO mice exhibited significant reduction in size, weight, length, and in long bones. At P0, the growth plates of EFNB2Col2 KO mice displayed increased type X collagen, disorganized hyphertrophic zone, and decreased mineralization. At P15, mutant mice demonstrated a significant reduction in VEGF and TRAP at the chondro-osseous junction and a delay in the secondary ossification, including a decrease in bone volume and trabecular thickness. At P21 and 8 weeks old, EFNB2Col2 KO mice exhibited reduced bone mineral density in the total skeleton, femur and spine. One-year-old EFNB2Col2 KO mice demonstrated OA phenotypic features in both the knee and hip. By P15, 27 % of the EFNB2Col2 KO mice developed a hip locomotor phenotype, which further experiments demonstrated reflected the neurological midline abnormality involving the corticospinal tract. Conclusion This in vivo study demonstrated, for the first time, that EFNB2 is essential for normal long bone growth and development and its absence leads to a knee and hip OA phenotype in aged mice.